ECHOCARDIOGRAPHIC CHANGES IN LEFT-VENTRICULAR DIMENSIONS AND LEFT-VENTRICULAR MASS IN BREAST CANCER PATIENTS SCHEDULED TO RECEIVE ANTHRACYCLINES - Gigovska Dimova, Irena (Journal of Morphological Sciences; Vol 7 No 1 (2024): JMS, 2024)
Anthracyclines (AT) are the cornerstone of adjuvant chemotherapy in breast cancer (BC) patients. Certain demographic parameters and risk factors predispose to anthracycline-induced cardiotoxicity (ATIC). Close echocardiography monitoring is crucial in diagnosing early cardiac changes, thus preventing further adverse cardiac events and withholding the cancer therapy. This study aims to assess possible changes in left ventricular (LV) dimensions, wall thicknesses and LV mass according to certain demographic characteristics and cardiovascular (CV) risk factors, as well as their relations in patients with BC receiving ATs. We present 30 patients with BC receiving ATs. Demographic parameters and risk factors are: age, body mass index, obesity, hypertension, diabetes, physical activity, risk for AT cardiotoxicity and total AT dose. The echocardiographic parameters followed are LV end-diastolic (LVDd) and end-systolic dimension (LVDs), wall thickness; interventricular septum (IVSd) and posterior wall (PW), as well as LV mass (LVM) and relative wall thickness. Statistical analysis included SPSS v.25.0 LV end-diastolic dimension (LVEDd) significantly increased at the control evaluation (p=0,026). Correlation between the differences in LVEDd and LVEDs between the two visits showed significant relation of the increase with higher indexed AT dose (p=0,007, p=0,030). Higher indexed AT dose was independent predictor for increased both LVEDd and LVEDs at the control evaluation. AT provoke significant echocardiography changes in BC patients and frequent surveillance provides assessment of early changes as an introduction to CTRCD. Further investigation is needed for a more sensitive ATIC discussion. Keywords: anthracyclines, breast cancer, echocardiography, left ventricular dimensions, left ventricular mass.